2022
DOI: 10.20517/cdr.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the molecular mechanisms of gastric cancer stem cell in drug resistance of gastric cancer

Abstract: Gastric cancer (GC) is one of the most common causes of cancer-related death worldwide, and gastric cancer stem cells (GCSCs) are considered as the major factor for resistance to conventional radio- and chemotherapy. Accumulating evidence in recent years implies that GCSCs regulate the drug resistance in GC through multiple mechanisms, including dormancy, drug trafficking, drug metabolism and targeting, apoptosis, DNA damage, epithelial-mesenchymal transition, and tumor microenvironment. In this review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 167 publications
(229 reference statements)
0
2
0
Order By: Relevance
“… 6 , 7 Identifying the molecular mechanisms that lead to the progression and metastasis of GC tumors is crucial in developing practical therapeutic approaches for treating this malignancy. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 Identifying the molecular mechanisms that lead to the progression and metastasis of GC tumors is crucial in developing practical therapeutic approaches for treating this malignancy. 8 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Identifying the molecular mechanisms that lead to the progression and metastasis of GC tumors is crucial in developing practical therapeutic approaches for treating this malignancy. 8 Accumulating investigations have indicated that besides genetic and epigenetic mechanisms, microRNAs (miRNAs) may regulate various biological processes and be significant modulators of tumorigenesis in different cancers, including GC, through post-transcriptional regulation of tumor suppressors and oncogenes. 2,9 miRNAs are a group of endogenous non-coding and regulatory RNAs with an estimated length of 18-22 nucleotides that play an important role in the negative regulation of gene expression, mainly by binding to the 3'UTR regions of the target mRNAs and occlusion of their translation.…”
Section: Introductionmentioning
confidence: 99%